2017
DOI: 10.1002/chem.201605819
|View full text |Cite
|
Sign up to set email alerts
|

Different Gelation and Self‐Sorting Properties of Two Isomeric Polyamides Owing to the Parallel versus Anti‐Parallel Alignment of Backbone Dipoles

Abstract: Two isomeric bottlebrush polyamides P-1 and A-1, with the same repeating monomer dipole units aligned along the polymer backbone in pseudo-parallel and pseudo-antiparallel fashion, respectively, were synthesized and characterized. Both polymers can form thermoreversible gels with aromatic solvents but P-1 was found to show inferior gelation strength compared with that of A-1. Furthermore, despite their close structural resemblance, a 1:1 mixture of the P-1 and A-1 polymers was shown to exhibit self-sorting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The second is that the presence of Hg 2+ can promote gel strength. As mentioned earlier, we reported that isomeric polymers having different molecular dipole alignment patterns could exhibit very different organogelating and self-sorting properties due to the additive dipole moment effect. However, in the present study, given that P-1 and P-2 are isomers that only differ in the relative disposition of the two alkyl side chains (i.e., the sterically bulkier R 2 and the smaller R 1 ), it is rather perplexing to find out that their different metal ion-responsive properties were due to such a small perturbation of the steric factor.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…The second is that the presence of Hg 2+ can promote gel strength. As mentioned earlier, we reported that isomeric polymers having different molecular dipole alignment patterns could exhibit very different organogelating and self-sorting properties due to the additive dipole moment effect. However, in the present study, given that P-1 and P-2 are isomers that only differ in the relative disposition of the two alkyl side chains (i.e., the sterically bulkier R 2 and the smaller R 1 ), it is rather perplexing to find out that their different metal ion-responsive properties were due to such a small perturbation of the steric factor.…”
Section: Resultsmentioning
confidence: 55%
“…It was noted that such differential properties of isomeric polymers, although not commonly seen, had been reported before. In previous cases, the origin of the differential properties was due to the different alignment patterns of the monomer dipoles along the polymer backbone, resulting in a difference in their organogelating and self-sorting properties …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another example, Chow et al reported the self-sorting of two polyamines with different dipole alignments. 142 These polymers aggregated via strong hydrogen bonding and π–π stacking to form gels. By mixing the two polymers upon heating and cooling to room temperature, self-sorted gels could be formed.…”
Section: Construction Methodsmentioning
confidence: 99%
“…Narcissistic self-sorting can also be manifested in the form of gel formation in multi-component gel system 30. In this context, we earlier showed that self-sorting occurred in a mixture of oligoamide gels 3 and 4 ,27 and also in polyamide gels 5 and 6 28. In the case of the oligamides, self-sorting was attributed to the difference in the number of amide units of the two structurally homologous hexamide 3 and dodecaamide 4 .…”
Section: Introductionmentioning
confidence: 95%